2015
DOI: 10.1111/apt.13427
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: transoral incisionless fundoplication vs. sham intervention to control chronic GERD

Abstract: SUMMARY BackgroundUntil recently only two therapeutic options have been available to control symptoms and the esophagitis in chronic gastro-oesophageal reflux disease (GERD), i.e. lifelong proton pump inhibitor (PPI) therapy or anti-reflux surgery. Lately, transoral incisionless fundoplication (TIF) has been developed and found to offer a therapeutic alternative for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 35 publications
5
74
0
Order By: Relevance
“…One-hundred and twenty-nine patients were randomized at eight academic and community hospitals across the US (87 TIF 2.0/placebo and 42 sham/PPI). Patients with troublesome regurgitation despite daily PPI use with three validated GERD-specific symptom (9), was a multi-center, double-blind, shamcontrolled randomized trial comparing the efficacy of TIF 2.0 against a sham procedure in GERD patients who were chronic PPI users. The primary outcome was the time to 'treatment failure' during the first six months postintervention.…”
Section: Resultsmentioning
confidence: 99%
“…One-hundred and twenty-nine patients were randomized at eight academic and community hospitals across the US (87 TIF 2.0/placebo and 42 sham/PPI). Patients with troublesome regurgitation despite daily PPI use with three validated GERD-specific symptom (9), was a multi-center, double-blind, shamcontrolled randomized trial comparing the efficacy of TIF 2.0 against a sham procedure in GERD patients who were chronic PPI users. The primary outcome was the time to 'treatment failure' during the first six months postintervention.…”
Section: Resultsmentioning
confidence: 99%
“…The TF procedure creates a full-thickness, partial esophagogastric fundoplication above the Z -line, with fastener fixations extending longitudinally up to 3.5 cm and circumferentially between 270° and 330° [11]. Published randomized controlled multicenter double-blind and open-label studies have demonstrated the superiority of the TF procedure as compared to high-dose PPI therapy and/or sham procedure in eliminating troublesome regurgitation and a range of classic and atypical manifestations of chronic GERD up to 12 months post-TF in subgroups of patients with hiatal hernias ≤2 cm [1215]. Importantly, in more than 17,000 procedures performed to date, TF has maintained a solid safety record with virtual absence of associated new onset of dysphagia and gas bloat [1215].…”
mentioning
confidence: 99%
“…EsophyX offers advantages over surgery [14][15][16][17], in particular the absence of incision and thus a faster remission, as well as fewer complications in the short and long term compared to the undesirable side effects associated with laparoscopic anti-reflux procedure compromising the results in some patients. Currently published literature suggests that incidence of persistent side effects after TIF is low [4][5][6]. This technique does not affect other future therapeutic options.…”
Section: Discussionmentioning
confidence: 91%
“…With no incision, no dissection and excellent safety profile, the procedure is performed with fewer complications than conventional ARS [5]. A novel device the EsophyX system with SerosaFuse fasteners (EndoGastric Solutions, Redmond, WA, USA) was designed to reconstruct a valve through tailored delivery of multiple fasteners during a single-device insertion [6,7]. This article presents results at 12 months from a prospective trial with 8 patients and was intended to further evaluate the safety and efficacy of the TIF procedure using the EsophyX system.…”
Section: Introductionmentioning
confidence: 99%